On the Natures of Thermally Induced Ultrasonic Emission from Nanofilm. Issue 1 (March 2021) - Hu, Hanping; Zhang, Kai; Wang, Dongdong
Abstract: Thermo-acoustic (TA) ultrasound has lots of advantages over traditional electric-acoustic ultrasound. In this work, by using a full-field formulas derived for acoustic field of TA emission from arbitrary source based on a thermally-mechanically coupled model, the basic natures of TA emission from nanofilm are studied via carbon nanotube (CNT) film. It is found that the TA sound pressure level (SPL) is fluctuated in near field and attenuated in far field, the SPL fluctuation in near field results from the interference of TA waves emitted from every element of film, which directly leads to the existence of, in point of technique, the most important nature of TA wave--flat frequency response at certain condition, and in far field, all the sound-emitting films can be regarded as point sources. These researches are significant for understanding TA wave and developing a variety of TA devices.